PENGARUH TERAPI RELAKSASI OTOT PROGRESIF TERHADAP KUALITAS TIDUR PADA LANSIA - Evi Royani; Fera Siska (Jurnal Kesehatan dan Pembangunan, 2023)
Aging (getting old) is a process of slowly disappearing the ability of the network to repair itself or replace and maintain its normal function so that it cannot survive infection and repair the damage suffered. The aging process is a continuous (continuous) process that naturally starts from birth and is generally experienced by all living things. As you get older, the body will experience a decrease and change, especially in the function of organs and body systems, so progressive muscle relaxation therapy is carried out to obtain relaxation for the purpose of reducing signs and symptoms such as pain, muscle stiffness, anxiety and insomnia. The purpose of this study was to determine the effect of progressive muscle relaxation therapy on sleep quality in the elderly. The research method was quantitative using a pre-experimental design approach (one group pre-post test design). Where in this study the sample was given a pretest (initial observation) before being given an intervention, after that an intervention was given, then a post-test (final observation) was carried out. The results of this study used a paired t-test which was conducted to find out whether there is an effect of progressive muscle relaxation therapy on sleep quality in the elderly. The results of the t-test in this study were found to be significant at 0.000 (p value <0.05). meaning that there is an effect of progressive muscle relaxation therapy on sleep quality in the elderly. The results of this study can be used as reference material and add to the literature at STIKES Mitra Adiguna Palembang, especially journals and materials that support writing scientific papers related to sleep quality in the elderly